Development and validation of the Food Disgust Scale. (January 2018) - Hartmann, Christina; Siegrist, Michael
Highlights: The psychometrically sound Food Disgust Scale (FDS) was developed. The FDS is a multidimensional measure of different types of food disgust. The FDS is associated with food neophobia, picky eating, and germ aversion. FDS scores and the number of food-borne illnesses are positively correlated. The FDS incrementally predicts willingness to eat insects over and above food neophobia. Abstract: The function of disgust as a pathogen avoidance promoter in the food domain is not well understood. One problem is that no food-specific disgust scale is available. Thus, we developed and validated the Food Disgust Scale (FDS) through a series of five studies. The FDS is a self-report measure that enables the assessment of an individual's emotional disposition to react with disgust to certain food-related (offensive) stimuli. Exploratory and confirmatory factor analyses were used to develop eight FDS subscales that represent unique types of food disgust: animal flesh, poor hygiene, human contamination, mold, decaying fruit, fish, decaying vegetables, and living contaminants. The subscales showed good internal consistencies across three different adult samples ( N between 170 and 527). Alongside the 32-item version, an 8-item composite measure was developed and tested. Validity was supported by correlational analysis between the revised version of the Disgust Scale, germ aversion, food neophobia, picky eating, and individuals' number of food-borne illnesses in the last five years. In addition, two-week test-retest reliability was very good. Incremental validity was supported in an eating experiment (i.e., willingness to eat insect-based food). The new scale will not only help improve the understanding of how food disgust shapes people's food behavior in a functional and dysfunctional way, but will also help enhance the understanding of consumer acceptance of new foods and food technologies.